Peningkatan Efisiensi Kerja Guru Melalui Pembuatan Aplikasi Rapor Berbasis Komputer - Romy Budhi Widodo; Mochamad Subianto; Grace Imelda (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
The domain of the activity is technology for the society whereas the focus is practical computer science for the society. The background of our activity is based on the needs of YPK junior high school in Malang city, Indonesia. The school need to develop computer-based school report card and also daily grade card for teachers. The method for software/application development is spiral model which consist of the cycle of system identification, risk analysis, and enhancement of the prototype to be an operational prototype. Evaluation of the product was based on the Computer System Usability Questionnaire (CSUQ) from IBM. The CSUQ using 5 scale of Likert scale contains three categories: 1) system usefulness (SYSUSE), 2) information quality (INFOQUAL), and 3) interface quality (INTERQUAL). The mean rankÃ¢â‚¬â„¢s result in order from the greatest to the lowest is SYSUSE, INTERQUAL, and INFOQUAL, respectively. It was reported that SYSUSE category was superior to INFOQUAL (U = 3369.5, p = 0.0005). Overall, the user satisfaction score is 78.4%, which is in the Ã¢â‚¬Å“worthyÃ¢â‚¬Â category